THEORETICAL AND METHODOLOGICAL ASPECTS OF INVESTMENT REAL ESTATE ACCOUNTING - IVANCHENKOVA, LARYSA; LAGODIIENKO, NATALIA; UZHVA, ALLA; SIEROVA, IRYNA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article systematizes and generalizes theoretical and methodological aspects of investment real estate accounting. Approaches to investment property identification are generalized. Classification features and criteria for distinguishing between operating and investment real estate are highlighted. The division of real estate into investment and operating real estate should be based not on how such real estate is used today, but on how (for what purpose) it is planned to use it in the future. To do this, the accountant must have documents such as: contracts, orders, protocols, any planning documents (business plan, financial plan, etc.) that allow to conclude on the further use of real estate. The conditions for recognizing fixed assets as investment property are defined, in particular: they are used exclusively for the purpose of receiving lease payments (only from operating lease, temporary, without transfer of ownership or lease for most of the useful life of such objects ); and / or they are used to increase equity (for example, they may be held with the prospect of rising property values and subsequent possible sales, but not for 12 months, but much longer, most likely indefinitely).A list of generally accepted objects that are recognized as investment property has been established. The reflection of investment real estate on accounting accounts is considered. Methodological approaches to the assessment of investment real estate in accounting are systematized. Purchased or created investment property is credited to the balance sheet at its original cost. Its calculation is quite similar to the original cost of fixed assets. At the balance sheet date, investment property can be carried using one of the two methods included in the entity's accounting policy: at cost less accumulated depreciation and impairment losses on investment property and at fair value. It is proved that the accounting of investment real estate at the original (residual) value is similar to the accounting of fixed assets. Differences of reflection in the accounting of investment real estate at initial cost from fixed assets are allocated. It is emphasized that the Tax Code currently does not contain special rules for accounting for investment property.
Keywords: real estate; investment real estate; operating real estate; fixed assets; land